SIMRS Network Security Simulation Using Snort IDS and IPS Methods - Wahyu Wijaya Widiyanto (Indonesian of Health Information Management Journal (INOHIM), 2022)
AbstractHospital information systems have an essential role in clinical and administrative services. This triggers an innovation that supports an integrated quality measurement data management system by integrating the Hospital Management Information System (SIMRS). SIMRS can be implemented locally or in the cloud, using the network to exchange data and information. Along with the current development of Information Technology, information security is very important, especially on a network connected to the internet. But what is unfortunate is that developments in the security system itself do not accompany the imbalance between each technological development. This study aims to overview techniques for securing network computers from various attacks through network security simulations. The research method used is using Snort as a detector to perform security on computer networks, while as a system for detecting and preventing intruders on computer network servers using the Intrusion Detection Systems (IDS) and Intrusion Prevention Systems (IPS) methods. This study concludes that the IDS system with Snort simulated can detect attacks with the same average accuracy value of 99.97% and produce an average server response time value by good snort rules (1 client is 0.50 seconds, 2 clients are 0.32) seconds.Keywords: network security, snort, IDS, IPS  AbstrakSistem informasi rumah sakit memiliki peran penting dalam pelayanan klinis dan administrasi. Hal ini memicu inovasi yang mendukung sistem pengelolaan data pengukuran mutu yang terintegrasi dengan mengintegrasikan Sistem Informasi Manajemen Rumah Sakit (SIMRS). Implementasi SIMRS dapat dilakukan secara lokal maupun cloud, keduanya menggunakan jaringan untuk bertukar data dan informasi. Seiring dengan perkembangan Teknologi Informasi saat ini, keamanan suatu informasi menjadi sangat penting terutama pada suatu jaringan yang terkoneksi dengan internet. Namun yang disayangkan, ketimpangan antara setiap perkembangan teknologi tersebut tidak dibarengi dengan perkembangan sistem keamanan itu sendiri. Penelitian ini bertujuan untuk memberikan gambaran tentang teknik pengamanan jaringan komputer dari berbagai jenis serangan melalui simulasi keamanan jaringan. Metode penelitian yang digunakan adalah menggunakan Snort sebagai pendeteksi untuk melakukan pengamanan pada jaringan komputer, sedangkan sebagai sistem untuk mendeteksi dan mencegah penyusup pada server jaringan komputer menggunakan metode Intrusion Detection Systems (IDS) dan Intrusion Prevention Systems (IPS). Kesimpulan dari penelitian ini adalah sistem IDS dengan simulasi Snort dapat mendeteksi serangan dengan nilai akurasi rata-rata yang sama yaitu 99,97%, dan menghasilkan nilai rata-rata waktu respon server dengan aturan snort yang baik (1 client adalah 0,50 detik, 2 client adalah 0,32) detik.Kata Kunci: keamanan jaringan, snort, IDS, IPS